Phenotypic identification of Metallo-ß- lactamase resistance Gram negative bacteria from a clinical specimen in Sidama, Ethiopia - Tsegaye Alemayehu; Wondwesson Abera; Musa Mohammed Ali; Bethelihem Jimma; Henok Ayalew; Limenih Habte; Frezer Teka; Demissie Asegu (PLoS ONE, 2025)
Background Metallo-beta lactamase resistance is one of the carbapenem resistances that worsen the world nowadays. A new variant of carbapenem-resistant has only limited reports from Africa including Ethiopia. This study aimed to determine Metallo -ß- lactamase resistance Gram-negative bacteria in Hawassa University Comprehensive Specialized Hospital January–June 2023. Method A cross-sectional study was conducted in which consecutive patients infected with Gram-negative bacteria were included in the study. A structured questionnaire was used to collect the data with oriented nurses if the patients/or caregivers gave consent to participate in the study. Clinical specimens are processed based on the standard operating procedure of the Microbiology laboratory and Clinical laboratory standard institute guidelines. Culture and sensitivity testing was used to isolate the bacteria. Gram staining and biochemical tests was used to identify the bacteria to genus and species. Kirby disc diffusion technique was used to determine the susceptibility of antibiotics. Statistical Software for Social Science (SPSS) version 21 is used for data entry and analysis. Descriptive statistics and logistic regression were used to interpret the data. The odds ratio at 95% confidence interval (CI) and p-value < 0.05 were taken as a statistically significant association. Result Our study included 153 isolates from different specimens, 83 (54.2%) were from male patients and 70 (45.8%) were from females. Klebsiella pneumonia was the predominant 43, followed by Escherichia coli 32, Acinetobacter spp 25, Pseudomonas spp 15, Enterobacter agglomerus 9, Klebsiella ozaenae 6, Enterobacter cloacae 5, Klebsiella oxytoca 4, (Klebsiella rhinoscleromatis, Proteus mirabilis and Morganella morganii) 3, Providencia stuartii 2 and (Citrobacter spp & Proteus vulgaris) 1. The rates of multi, extensive and pan-drug resistance bacteria accounted for 128/153 (83.7%), 77 /153(50.3%), and 26/153 (17.0%), respectively. Carbapenem resistance was 21 (13.7%), of this 7.2% were Enterobacteriaceae, 5.2% were Acetinobacter spp. and 1.3% Pseudomonas spp. Metallo-beta-lactamase was 17 (11.1%), of this, Enterobacteriaceae were 9(5.9%), Acetinobacter spp. 7(4.6%), and Pseudomonas spp. 1(0.7%). There were no variables statistically significantly associated with metallo-beta-lactamase-resistant. Conclusion Our study revealed that Metallo-beta-lactamase resistance was circulating in the study area. There was a high rate of carbapenem resistance, multi, extensive and pan-drug resistance. Therefore, a measure should be taken to alleviate the emerging threat that leaves the patients without the option of treatment.